Risk Factors for Intestinal Barrier Impairment in Patients With Essential Hypertension - Li, Cao; Xiao, Ping; Lin, Da; Zhong, Hao-Jie; Zhang, Ran; Zhao, Zhi-gang; He, Xing-Xiang (Frontiers in Medicine, 2021)
Background: Previous studies have indicated an association of hypertension with intestinal barrier dysfunction in mice model. The present study aims to investigate the association between hypertension and intestinal barrier impairment in human, and identify the novel potential risk factors for hypertension. Methods: Medical data from consecutive inpatients were retrospectively pooled from patient records. We compared serum markers of intestinal barrier (diamine oxidase [DAO], lipopolysaccharide [LPS], and D-lactate) between patients with and those without hypertension. Moreover, the associations between intestinal barrier markers and cardiovascular risk, hypertension history, blood pressure control, hypertensive complications, and antihypertensive medications history were also analyzed. Results: Overall, 106 hypertensive and 251 normotensive subjects were included. Patients with hypertension had a higher level of DAO (28.30% vs. 18.73%, P = 0.044) and LPS (22.64% vs. 11.16%, P = 0.005). In hypertensive patients, multivariate logistic regression analyses showed that, long hypertension history (≥20 years), poor control of diastolic blood pressure, cardiac and renal complications, and use of multiple antihypertensive medications were risk factors for elevated DAO, while use of multiple antihypertensive medications was a risk factor for elevated D-lactate (P < 0.05). Conclusions: Hypertension is associated with impairment of intestinal barrier, especially in patients with long duration, poor blood pressure control, cardiac and renal complications, and use of multiple antihypertensive medications. The current study indicates that intestinal barrier dysfunction might be a potential predictor for hypertension.